THE INFLUENCE OF INDUSTRY TYPE, ENVIRONMENTAL MANAGEMENT PERFORMANCE, AND CARBON INTENSITY ON CARBON EMISSION DISCLOSURE - Woen, Esperansya Desmonda; Setijaningsih, Herlin Tundjung (International Journal of Application on Economics and Business, 2025)
The IPCC AR6 Working Group I report highlights that greenhouse gas emissions, particularly those generated by human activities, are the primary drivers of global warming, emphasizing the importance of better environmental accountability. In Indonesia, PSAK allows entities to issue separate environmental reports from their financial statements, particularly in industries where environmental considerations are critical. However, there is a significant disparity in the disclosure obligations for carbon emissions across various sectors. This study aims to explore the influence of industry type, environmental management performance, and carbon intensity on carbon emission disclosure among companies listed in the IDX30 index. The study uses a sample of 16 companies for the period from 2019 to 2021, selected through purposive sampling. The data were processed using Eviews 12 software. The findings indicate that all three independent variables collectively influence carbon emission disclosure. However, when tested individually, industry type does not have a significant impact and shows a positive correlation with carbon emission disclosure. Similarly, carbon intensity does not have a significant effect and exhibits a negative relationship with carbon emission disclosure. In contrast, environmental management performance shows a significant positive effect on carbon emission disclosure. These findings indicates that higher environmental management performance is closely related to higher transparency and more comprehensive carbon emission disclosures.